A world worth saving - Lukoff, Kyle (Dial Books for Young Readers, an imprint of Penguin Random House LLC, 2025)
After coming out as trans, fourteen-year-old A is forced to attend weekly Save Our Sons and Daughters meetings, where he uncovers the terrifying truth that the group is run by a demon feeding on their pain and is part of a larger, darker force preying on the world's vulnerable.